Jews in the early modern world - Bell, Dean Phillip, 1967- (Rowman & Littlefield, 2008)
Jews in the Early Modern World argues that the years between 1400 and 1700 represented a discrete, cohesive and important period in Jewish history. Given the significant demographic shifts that began just before and ended just after this period, remarkable changes occurred in the history and experiences of Jews around the world. This volume begins with a broad context of Jewish experiences under medieval Christianity and Islam. It then turns to the early modern period, first providing an overview of Jewish demography and settlement. Next, the nature and structure of Jewish community and social structures in the early modern period are explored. In the final two chapters, this book presents a broad overview of Jewish religious and cultural life and Jewish relations with non-Jews throughout the early modern period. - Publisher.